Description of the nymph of Massartella alegrettae Ulmer, 1943 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) with a key to Massartella Lestage, 1930 nymphs - Souto, Paula Malaquias; Da-Silva, Elidiomar Ribeiro; Nessimian, Jorge Luiz (Zootaxa, 2013)
The South American genus Massartella Lestage, 1930 is composed of five species. Massartella alegrettae Ulmer, 1943 is the only species with the nymph unknown. In this paper, we describe the nymph of M. alegrettae based on specimens from the state of São Paulo, Brazil. This is the first record of the species from southeastern Brazil. The nymph can be easily recognized by the gills present on segments I-V, with dark gray membrane and without apical processes.